(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the national economy, thin-walled structures such as shells are widely used, which leads to the fact that they are subject to increasingly stringent requirements, which are associated not only with saving money and materials during the construction of various structures, but also with the creation of structures of minimum weight. In this regard, the issues of optimal design of underground structures are an urgent task.